An electrochemical cell for operando bench‐top X‐ray diffraction. Issue 2 (26th February 2019) - Sottmann, Jonas; Pralong, Valérie; Barrier, Nicolas; Martin, Christine
Abstract : An X‐ray transparent electrochemical cell with dense glassy carbon windows (Sigradur‐G) for operando bench‐top X‐ray diffraction in reflection geometry is demonstrated. Abstract : An X‐ray transparent electrochemical cell for operando bench‐top X‐ray diffraction in reflection geometry is presented. Dense glassy carbon (Sigradur‐G) is used as an X‐ray transparent window. The cell and dedicated sample holder are easy to handle and cost efficient thanks to their simple designs. To demonstrate the performance of this new Swagelok‐type operando cell, diffractograms were collected during cycling of the cathode material Li x Mn2 O4  ( x ≤ 1) in a lithium‐ion battery. During charging/delithiation, three spinel phases with evolving lattice parameters were found. This observation confirms the expected mixed two‐phase and solid‐solution behaviour and thereby validates our experimental setup. The presented low‐cost setup may enable further battery research units to access operando X‐ray diffraction data for characterization of structural phenomena during battery cycling and degradation mechanisms during prolonged cycling, which will lead to improvement of the battery technology.